Ketogenic Diet Modulates NAD+-Dependent Enzymes and Reduces DNA Damage in Hippocampus - Elamin, Marwa; Ruskin, David N.; Masino, Susan A.; Sacchetti, Paola (Frontiers in Cellular Neuroscience, 2018)
The ketogenic diet’s (KD) anti-seizure effects have long been documented. Recently, its therapeutic potential in multiple neurodegenerative and neurodevelopmental disorders has emerged. Yet experimental evidence for a fundamental mechanism underlying beneficial effects across numerous diseases remains lacking. We previously showed that feeding rats a KD produced an early (within 2 days) and persistent elevation of hippocampal nicotinamide adenine dinucleotide+ (NAD+), an essential metabolic coenzyme and signaling molecule. NAD+ is a marker of cellular health and a substrate for enzymes implicated in longevity and DNA damage repair such as sirtuins and poly-ADP ribose polymerase-1 (PARP-1). As a result, activation of NAD+-dependent enzymes’ downstream pathways could be the origin of KD’s broad beneficial effects. Here rats were fed ad libitum regular chow or KD for 2 days or 3 weeks and the levels of hippocampal sirtuins, PARP-1, and the oxidative DNA damage marker 8-hydroxy-2’-deoxyguanosine were quantified. We found a significant immediate and persistent increase in the collective activity of nuclear sirtuin enzymes, and a significant augmentation of Sirt1 mRNA at 2 days. Levels of PARP-1 and 8-hydroxy-2’-deoxyguanosine decreased after 2 days of treatment and further declined at 3 weeks. Our data show that a KD can rapidly modulate energy metabolism by acting on NAD+-dependent enzymes and their downstream pathways. Thus, therapy with a KD can potentially enhance brain health and increase overall healthspan via NAD+-related mechanisms that render cells more resilient against DNA damage and a host of metabolic, epileptic, neurodegenerative, or neurodevelopmental insults.